Seed producers’ groups in Nepal - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Seed producers’ groups in seven villages in Lamjung, Tanahun, and Gorkha districts were formed in 2012. Since then, the production of lowland rice seeds doubled and upland rice seeds more than tripled. The groups have also been a means for CURE to introduce new varieties to the communities through participatory varietal selection approaches. The groups were instrumental to improved seed exchanges and information sharing among farmers as well as the increase in women’s participation in farming.